2019
DOI: 10.5194/acp-2019-792
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fossil fuel combustion, biomass burning and biogenic sources of fine carbonaceous aerosol in the Carpathian Basin

Abstract: <p><strong>Abstract.</strong> Fine-fraction aerosol samples were collected, air pollutants and meteorological properties were measured in-situ in regional background environment of the Carpathian Basin, a suburban area and central part of its largest city, Budapest in each season for 1 year-long time interval. The samples were analysed for PM<sub>2.5</sub> mass, organic carbon (OC), elemental carbon (EC), water-soluble OC (WSOC), radiocarbon… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 70 publications
(108 reference statements)
1
8
0
Order By: Relevance
“…The strongest connections are related to cold air masses above the basin which generate a lasting T inversion and relatively shallow planetary boundary layer (cold air pool). It confirms that the daily evolution of regional meteorology can have higher influence on atmospheric concentrations than the source intensities under such conditions (Salma et al, 2020a). The curves for PM2.5 mass and N6-1000 confirmed that there is week association between these two types of aerosol metrics (de Jesus et al, 2019).…”
Section: Time Series Of Concentrationssupporting
confidence: 61%
See 3 more Smart Citations
“…The strongest connections are related to cold air masses above the basin which generate a lasting T inversion and relatively shallow planetary boundary layer (cold air pool). It confirms that the daily evolution of regional meteorology can have higher influence on atmospheric concentrations than the source intensities under such conditions (Salma et al, 2020a). The curves for PM2.5 mass and N6-1000 confirmed that there is week association between these two types of aerosol metrics (de Jesus et al, 2019).…”
Section: Time Series Of Concentrationssupporting
confidence: 61%
“…At the same time, PM10 mass represents disintegration sources, e.g. windblown or resuspended soil, crustal rock, mineral and roadside dust particularly under dry weather conditions, agricultural activities in the region and material wear (Putaud et al, 2010;Salma et al, 2020a).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The typical mean contribution of biogenic sources to the total carbon in the PM2.5 size fraction was the second largest with a share of ca. 40 % (Salma et al, 2020). Unfortunately, there is no experimental information available on absolute concentrations or amounts of VOC in the area.…”
Section: Event-day-to-non-event-day Ratiosmentioning
confidence: 99%